Maigret and the wine merchant - Simenon, Georges, 1903-1989 (A Harvest/HBJ book, 1980)
The richest wine merchant in Paris is found dead--shot in front of an elegant house where discreet clients rent rooms for discreet purposes. Everything seems to point to a crime sparked by jealousy. But Maigret is surprised to find a curious absence of shock or grief in the vicitm's family and colleagues, and further investigation into the life and habits of the murdered man reveals some singularly unlovable traits.